Isothermal kinetic study of nitric oxide adsorption and decomposition on Pd(111) surfaces: molecular beam experiments - Thirunavukkarasu, K; Thirumoorthy, K; Libuda, X; Gopinath, Chinnakonda S. (Journal of Physical Chemistry B, 2005)
The kinetics of NO adsorption and dissociation on Pd(111) surfaces and the NO sticking coefficient (S-NO) were probed by isothermal kinetic measurements between 300 and 525 K using a molecular beam instrument. NO dissociation and N-2 productions were observed in the transient state from 425 K and above on Pd(l 11) surfaces with selective nitrogen production. Maximum nitrogen production was observed between 475 and 500 K. It was found that, at low temperatures, between 300 and 350 K, molecular adsorption occurs with a constant initial SNO of 0.5 until the Pd(I 11) surface is covered to about 70-80% by NO. Then SNO rapidly decreases with further increasing NO coverage, indicating typical precursor kinetics. The dynamic adsorption-desorption equilibrium on Pd(I 11) was probed in modulated beam experiments below 500 K. CO titration experiments after NO dosing indicate the diffusion of oxygen into the subsurface regions and beginning surface oxidation at >= 475 K. Finally, we discuss the results with respect to the rate-limiting character of the different elementary steps of the reaction system.